Dual-functional NIR/UV-shielding poly(lactic acid) nanocomposite films through CWO@PDA core–shell nanoparticles. (20th July 2022) - Yan, Zhendong; Wang, Yang; Li, Ting; Xu, Pengwu; Huang, Jing; Jiang, Jie; Zhang, Xuhui; Xia, Bihua; Wang, Shibo; Dong, Weifu
Abstract : Fabrication of dual-functional NIR/UV-shielding PLA nanocomposite films by constructing interfacial stereocomplex crystallites. Abstract : Nanoparticles with ultraviolet/near-infrared (UV/NIR) shielding ability have great potential in the application research of energy-saving materials. In this study, we prepared dual-functional UV/NIR-shielding poly(lactic acid) (PLA) composite films. Firstly, Cs x WO3 @polydopamine (CWO@PDA) nanoparticles with core–shell structures were formed by dopamine self-polymerization on the surface of CWO, and then CWO@PDA- g -PLLA nanoparticles were successfully prepared by ring-opening polymerization with l -lactide as a raw material. Finally, PDLA/CWO@PDA- g -PLLA composite films containing different proportions of CWO@PDA- g -PLLA nanoparticles were fabricated via a solvent casting method. The results showed that these films have an excellent UV shielding performance and strong absorption in the NIR region (800–2500 nm). When 1.5 wt% of CWO@PDA- g -PLLA nanoparticles was added, the near-infrared transmittance of the composite films decreases significantly from 79.7% to 29.8%. More importantly, the nanoparticles can be used as a heterogenous nucleator to enhance the HC crystallization of PDLA and form stereocomplex crystallites between PDLA and CWO@PDA- g -PLLA nanoparticles which improved the mechanical properties. This study provided a new method for the preparation of PLA nanocomposites with excellent UV/NIR shielding function. These nanocomposites are promising for practical application on energy-saving windows.